Carcinoembryonic Antigen Related Cell Adhesion Molecule 6 Promotes Carcinogenesis of Gastric Cancer and Anti-CEACAM6 Fluorescent Probe Can Diagnose the Precancerous Lesions - An, Fangmei; Zheng, Chuwei; Zhang, Guoqiang; Zhou, Liangyun; Wu, Yuqing; Hou, Zheng; Zhou, Zhiyi; Chen, Ke; Zhan, Qiang (Frontiers in Oncology, 2021)
The diagnosis of precancerous lesions or early gastric cancer (EGC) is very important for patient survival. Molecular imaging is a visualized method that can easily and precisely diagnose tumors. However, there are currently few studies about molecular imaging diagnosis of EGC. Here, we studied the expression of carcinoembryonic antigen related cell adhesion molecule 6 (CEACAM6) in the progression of GC. Then, the regulatory roles of CEACAM6 in GC cells were investigated. Furthermore, both the fluorescent-labeled and near infrared molecular-labeled probes were synthesized, and the diagnostic value of anti-CEACAM6 probes in GC was evaluated in vivo using a GC mice model as well as in vitro using fresh dysplastic gastric mucosa obtained from endoscopic submucosal dissection (ESD) operations. Our study showed that CEACAM6 was over expressed in GC tissues compared to adjacent tissues, and the patients with higher CEACAM6 expression had lower survival time. Moreover, the CEACAM6 expression was higher in the dysplastic gastric mucosa than in the adjacent normal mucosa. CEACAM6 accelerated the growth, proliferation, and invasion of GC cells in the in vitro and in vivo studies. Moreover, up regulated CEACAM6 can induce the expression of proteins related to GC progression. Furthermore, the anti-CEACAM6 probes exhibited good affinity with GC cell lines. The probes can track tumors as well as metastases in the mice model in vivo, and can precisely identify the area of dysplastic gastric mucosa using specimens obtained from ESD operations by wide field fluorescent endoscopy. The surface micro features of the mucosa can also be observed using fluorescent micro endoscopy, and the degree of atypia can be distinguished by both the signal intensity and surface micro morphology. CEACAM6 is a key molecular marker in GC progression, and the anti-CEACAM6 probe-assisted fluorescent endoscopy may be a potential option for the diagnosis of precancerous.